Photoprotection and Antiaging Activity of Extracts from Honeybush (Cyclopia sp.)-In Vitro Wound Healing and Inhibition of the Skin Extracellular Matrix Enzymes: Tyrosinase, Collagenase, Elastase and Hyaluronidase - Anna Hering; Justyna Stefanowicz-Hajduk; Magdalena Gucwa; Bartosz Wielgomas; Jadwiga Renata Ochocka (MDPI AG, 2023)
Cyclopia sp. (honeybush) is an African shrub known as a rich source of polyphenols. The biological effects of fermented honeybush extracts were investigated. The influence of honeybush extracts on extracellular matrix (ECM) enzymes responsible for the skin malfunction and aging process-collagenase, elastase, tyrosinase and hyaluronidase-was analysed. The research also included assessment of the in vitro photoprotection efficiency of honeybush extracts and their contribution to the wound healing process. Antioxidant properties of the prepared extracts were evaluated, and quantification of the main compounds in the extracts was achieved. The research showed that the analysed extracts had a significant ability to inhibit collagenase, tyrosinase and hyaluronidase and a weak influence on elastase activity. Tyrosinase was inhibited effectively by honeybush acetone (IC50 26.18 ± 1.45 µg/mL), ethanol (IC50 45.99 ± 0.76 µg/mL) and water (IC50 67.42 ± 1.75 µg/mL) extracts. Significant hyaluronidase inhibition was observed for ethanol, acetone and water extracts (IC50 were 10.99 ± 1.56, 13.21 ± 0.39 and 14.62 ± 0.21µg/mL, respectively). Collagenase activity was inhibited effectively by honeybush acetone extract (IC50 42.5 ± 1.05 μg/mL). The wound healing properties of the honeybush extracts, estimated in vitro in human keratinocytes (HaCaTs), were indicated for water and ethanol extracts. In vitro sun protection factor (SPF in vitro) showed medium photoprotection potential for all the honeybush extracts. The quantity of polyphenolic compounds was estimated with the use of high-performance liquid chromatography equipped with diode-array detection (HPLC-DAD), indicating the highest mangiferin contents in ethanol, acetone and n-butanol extracts, while in the water extract hesperidin was the dominant compound. The antioxidant properties of the honeybush extracts were estimated with FRAP (2,4,6-Tris(2-pyridyl)-s-triazine) and DPPH (2,2-diphenyl-1-picrylhydrazyl) tests, indicating their strong antioxidant activity, similar to ascorbic acid for the acetone extract in both tests. The wound healing abilities, estimation of SPF in vitro and the direct influence on selected enzymes (elastase, tyrosinase, collagenase and hyaluronidase) of the tested honeybush extracts were analysed for the first time, indicating a high potential of these well-known herbal tea for antiaging, anti-inflammation, regeneration and protection of the skin.